Predicting atrial fibrillation recurrence after ablation in patients with heart failure: Validity of the APPLE and CAAP‐AF risk scoring systems. Issue 11 (18th October 2019) - Black‐Maier, Eric; Parish, Alice; Steinberg, Benjamin A.; Green, Cynthia L.; Loring, Zak; Barnett, Adam S.; Al‐Khatib, Sana M.; Atwater, Brett D.; Daubert, James P.; Frazier‐Mills, Camille; Hegland, Donald D.; Jackson, Kevin P.; et al.
Abstract: Background: Compared with medical therapy, catheter ablation of atrial fibrillation (AF) in patients with heart failure (HF) improves cardiovascular outcomes. Risk scores (CAAP‐AF and APPLE) have been developed to predict the likelihood of AF recurrence after ablation, have not been validated specifically in patients with AF and HF. Methods: We analyzed baseline characteristics, risk scores, and rates of AF recurrence 12 months postablation in a cohort of 230 consecutive patients with AF and HF undergoing PVI in the Duke Center for Atrial Fibrillation registry from 2009‐2013. Results: During a follow‐up period of 12 months, 76 of 230 (33%) patients with HF experienced recurrent AF after ablation. The median APPLE and CAAP‐AF scores were 1.5 ([Q1, Q3]: [1.0, 2.0]) and 4.0 ([Q1, Q3]: [3.0, 5.0]), respectively and were not different from those patients with and without recurrent AF. Freedom from AF was not different according to APPLE and CAAP‐AF scores. Discrimination for recurrent AF with the CAAP‐AF score was modest with a C‐statistic of 0.60 (95% CI 0.52‐0.67). Discrimination with the APPLE score was similarly modest, with a C‐statistic of 0.54 (95% CI: 0.47‐0.62). Conclusions: Validated predictive risk scores for recurrent AF after catheter ablation exhibit limited predictive ability in cohorts of AF and HF. Additional tools are needed to facilitate risk stratification and patient selection for AF ablation in patients with concomitant HF.